Magang Bersertifikat Community Intern di Zenius Education - Denisa Sabila; Muhammad Ghazi; Arya Pradipta (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
This Internship Report was written to explain the writer’s activities during her internship period in Zenius Education through Magang Bersertifikat Kampus Merdeka Program which was held by the Minsitry of Education. In this report, there would be an explanation about the company itself and the writer’s routinity as a part of the Community team. The explanation included were the distribution of jobs in Community, the writer’s daily job (That’s to manage Live Q&A Alumni Series Program), and also the process of making her Final Assignment with other Community Interns. The final assignment which named after UTBK Fest, was initiated to be a one-time event that involved the alumni and Zenius current user. It was a collaboration project with some other teams and was held on January 2022.